A Nonlinear Controller for Neutral Point Piloted (T-Type) Multilevel Inverter-Based Three-Phase Four-Wire DSTATCOM. (16th July 2022) - Swetha, K.; Sivachidambaranathan, V.
Abstract : In recent times, neutral point piloted (NPP) or half-leg T-type multilevel inverter (MLI) becomes a promising topology for medium-voltage high-power applications. This T-type MLI is the best substitute for diode clamped multilevel inverter (DCMLI) due to its simple structure and absence of clamping diodes. However, the neutral point voltage control or dc bus capacitors' balance of NPP T-type MLI is a challenging task. Therefore, this paper presents a nonlinear sliding mode controller (SMC) for dc-link voltage balance and reference current control in distribution static compensator (DSTATCOM). For this, a three-level T-type MLI-based three-phase four-wire DSTATCOM is considered to eliminate current-related power quality issues such as harmonics, reactive power, load unbalance, and neutral current. The proposed NPP T-type-based DSTATCOM is compared with DCMLI and active DCMLI-based DSTATCOMs in terms of switching losses and cost. Simulation studies are carried out in MATLAB Simulink environment and further corroborated with experimental studies. Furthermore, the ability of the proposed SMC-based controller is compared with the PI controller under different operating conditions.